An assessment of the impact of teachers’ digital competence on the quality of videos developed for the flipped math classroom - Moreno-Mediavilla, Daniel; Palacios Ortega, Alicia; Barreras, Álvaro; Pascual López, Virginia (Mathematics, 2020)
The aim of this research is to determine the impact of perceived Teachers' Digital Competence (TDC) on how well math teachers prepare the educational videos needed to put the flipped classroom model into practice. In preparing the videos, the teachers had to select pre-existing audiovisual material and then edit the content to adapt it to the flipped classroom. Described here is a non-experimental study of a sample of 50 teachers pursuing a Master's degree in Secondary School Math Education in Spain. This is a preliminary univariate descriptive study of the relationship between TDC and the quality of videos prepared. Possible correlations between these two variables and between the characteristics of the sample are also explored. In general, the teachers had an intermediate level of TDC and prepared satisfactory videos. Nevertheless, the videos were deficient in the sections related to their pedagogical and math instructional components. No correlation was observed between TDC and the quality of the videos prepared. These results indicate that the integration of technological, pedagogical, and math instructional components is more important for developing quality instructional videos than the technological component alone. Teacher training should incorporate elements which emphasize the application of technology to the pedagogical process of math instruction.
Keywords: Teachers’ Digital Competence; instructional video; flipped classroom; teacher continuing professional development; math; secondary education; JCR; Scopus